Investigation on synthesis and process control of microporous particle material - Huang, Xiani (2019)
With the increasing demands for portable electronic devices and the use of electrical vehicles (EVs) for green transport, the application of high energy density Lithium-ion batteries (LIBs) has been widely recognised. As an important part of Lithium-ion battery, LiNixCoyMn1-x-yO2 (NCM) cathode material, especially high nickel NCM material, has attracted much attention due to high capacity, low cost, good cycling stability and safety. Today, the preparation process of LiNixCoyMn1-x-yO2 is commercial and mature. The synthesis conditions of high nickel material are harsh and its surface activity is high, plus, its long synthesis time, which restricts its popularization and application. Hence, developing a simple and cost-effective method instead of the traditional preparation way is urgently needed. In this work, a Lobed Taylor-Couette reactor (LTC) has been applied to synthesize the NiCoMn hydroxide, a precursor of LiNixCoyMn1-x-yO2cathodic material used in batteries. A steady state is attained when the reaction time is about 3~4 times of the mean residence time. The effect of shear rate on the agglomerate shape and sizes of the hydroxides was studied. It was found that the particle size decreases with increasing from low shear rate to high shear rate while the morphology of particles changes from irregular to spherical-like in shapes. The molar ratio of NH3/MSO4 (0.4~1) would be desirable for getting spherical precursors. A relation correlating turbulent energy dissipation rate and the molar ratio of NH3/MSO4 is proposed for estimation of the particle sizes. Following the study on synthesis of the NiCoMn hydroxide, the electrochemical performances of synthesisedLiNi0.6Co0.2Mn0.2O2 cathode materials were evaluated. Calcination of (Ni0.6Co0.2Mn0.2)(OH)2 with LiOH at a proper temperature leads to a high tap-density of materials. The effect of various parameters such as stirring speed and molar ratio of NH3/MSO4 on the electrochemical performances of LiNi0.6Co0.2Mn0.2O2was investigated. It has been revealed from the present study that our developed material has been demonstrated to have good electrochemical stability. Based on the preceding studies, numerical simulation to predict the electrochemical performance of LiNi0.6Co0.2Mn0.2O2 during the discharge process was performed. In the simulations, an electrochemical Pseudo 2D model with modifications was adopted, taking the electrochemical reactions into consideration. The effects of calendaring and particle sizes on the physical and electrochemical property of LiNi0.6Co0.2Mn0.2O2 cathode were investigated using this model. The simulation results indicate that the estimated porosity by fitting the experimental data, which was used in the model, shows consistency for numerical simulation of electrochemical properties of the LIBs. Meanwhile, the simulation results have illustrated that decreasing the particle size of active materials can be beneficial to the enhancement of diffusion of the solid phase, characterized by an increase in the diffusion coefficient (Ds). The material doping was also explored, aiming to improve the electrochemical performance of LiNi0.6Co0.2Mn0.2O2 cathode material. The effects of the Mg doping for Ni on the structure and the electrochemical properties of Li(Ni0.6Co0.2Mn0.2)O2 samples are assessed. The use of the Rietveld refinement has shown that addition of a small amount of Mg will be beneficial to the lowering of the bonding distance of Li-O and M-O and increasing the structural stability of the material, thus to the improvement of the electrochemical performances of Li(Ni0.6Co0.2Mn0.2)O2.